Review on the application of imaging examination for brain injury in premature infants - Zhang, Qing; Zhou, Xihui (Frontiers in Neurology, 2023)
Brain injury of premature infants is the main factor leading to the decline of the quality of life of premature infants. The clinical manifestations of such diseases are often diverse and complex, lacking obvious neurological symptoms and signs, and the disease progresses rapidly. It is easy to miss the best treatment opportunity due to missed diagnosis. Brain ultrasound, computed tomography (CT), magnetic resonance imaging (MRI) and other imaging examination methods can help clinicians to diagnose and evaluate the type and extent of brain injury in premature infants to a certain extent, but the three examination methods have their own characteristics. This article briefly reviewed the diagnostic value of these three methods for brain injury in premature infants.